Feasibility Study of Developing a Zero-carbon-emission Green Deck in Hong Kong. (May 2017) - Ma, Tao; Yang, Hongxing; Lu, Lin; Qi, Ronghui
Abstract: This study examines the feasibility of utilizing renewable energy power generation technology to developing a zero-carbon-emission Green Deck. The power consumption of the deck, including lighting, ventilation and air-conditioning, is firstly estimated. Then the potential of solar photovoltaic (PV) module installation in roof and vertical façade is evaluated through simulation and theoretical calculation, demonstrating that it is highly possible to achieve the target of net-zero-energy consumption and zero carbon emission. Furthermore, the economic feasibility of the proposed PV system on the Green Deck has been studied.